2022
DOI: 10.4103/ijo.ijo_1652_22
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium hyaluronate eye drops combined with tobramycin, dexamethasone and pranoprofen eye drops in the treatment of dry eye after phacoemulsification

Abstract: Purpose: To investigate the clinical effect of sodium hyaluronate eye drops combined with tobramycin, dexamethasone, and pranoprofen eye drops in the treatment of dry eye after phacoemulsification. Methods: Medical records of 188 patients with dry eye after phacoemulsification, treated in our hospital from August 2020 to August 2021, were included and divided into groups based on the type of dry eye treatment. Patients in the control group ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Similar ndings were reported in the few earlier studies that assessed the bene t of adding sodium hyaluronate to the treatment regimen of DED after cataract surgery. 13,15,22 Chen et al 13 observed that sodium hyaluronate was able to restore the structure of the tear lm and improve the regularity of the corneal surface. In agreement with our study, Lu et al 15 found that combining sodium hyaluronate with pranoprofen, tobramycin, and dexamethasone improved the curative effect compared to when sodium hyaluronate was lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar ndings were reported in the few earlier studies that assessed the bene t of adding sodium hyaluronate to the treatment regimen of DED after cataract surgery. 13,15,22 Chen et al 13 observed that sodium hyaluronate was able to restore the structure of the tear lm and improve the regularity of the corneal surface. In agreement with our study, Lu et al 15 found that combining sodium hyaluronate with pranoprofen, tobramycin, and dexamethasone improved the curative effect compared to when sodium hyaluronate was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,22 Chen et al 13 observed that sodium hyaluronate was able to restore the structure of the tear lm and improve the regularity of the corneal surface. In agreement with our study, Lu et al 15 found that combining sodium hyaluronate with pranoprofen, tobramycin, and dexamethasone improved the curative effect compared to when sodium hyaluronate was lacking. Yang and Wang 22 reported that sodium hyaluronate combined with pranoprofen had effectively treated DED and was able to enhance tear secretion, keep ocular moisture, recover tear lm stability, and improve the patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation was conducted using the formula for comparing two independent proportions. Specifically, we used the formula based on the Z-test for proportions, taking into account the reported efficacy scores from a similar published study, 19 which found that adding sodium hyaluronate increased the efficacy scores from 88.9% to 99%. The minimum number of participants required in each group to achieve a statistically significant result with a confidence level of 95% (α level of 0.05) and a power of 80% was 68 patients in each group.…”
Section: Methodsmentioning
confidence: 99%